Konsep Pendidikan dalam Perspektif Muhammad Natsir - Firdaus (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
This study aims to determine the concept of education and Muhammad Natsir. The method used in this research is a qualitative method with a library research approach. The results of this study explain that education is something that is very important in human life. The urgency of education makes education experts give a lot of ideas in order to improve the quality of education itself. One of the national figures who cares about the world of education is Muhammad Natsir. Muhammad Natsir contributed many thoughts inorder to advance education in Indonesia. According to Natsir, education must be based on Tauhid. Eliminating monotheism in the world of education is a very big mistake and also a very big negligence. Muhammad Natsir also offers an integral direction of education. This means that in the world of education there is no longer any separation between religion and science. Islam has a concept of not separating religion and science. Separating religion and science means opening up opportunities to secularize science and also to secularize education. The integration of science will make the science in the garden bring people to know who the creator is.